A robust Fuzzy-PI pitch angle controller for wind turbine systems - S., Ahmed; S.B., Yaakob; F., Malek; M.A., Rashid (Trans Tech Publications, 2015)
This paper presents a robust Fuzzy-PI controller to adjust the pitch angle of a grid integrated wind turbine. The pitch angle mechanism of a turbine blade allows it rotate on its own axis so that it can protect itself from high wind gust and release excessive stress from the mechanical structure. Although a classical PI controller has been widely used for this purpose, they cannot assure generator stability. The proposed Fuzzy-PI control system uses three control inputs and nine membership functions to make decision on pitch angle output. A wind speed model is devised to simulate real life turbulent wind condition. The simulation results show that the Fuzzy-PI controller is more suitable for turbine operation if it is subjected to heavy turbulence.